The Rough Guide to Monocytes in Malaria Infection - Ortega-Pajares, Amaya; Rogerson, Stephen J. (Frontiers in Immunology, 2018)
While half of the world’s population is at risk of malaria, the most vulnerable are still children under five, pregnant women and returning travellers. Anopheles mosquitoes transmit malaria parasites to the human host; but how Plasmodium interact with the innate immune system remains largely unexplored. The most recent advances prove that monocytes are a key component to control parasite burden and to protect host from disease. Monocytes’ protective roles include phagocytosis, cytokine production and antigen presentation. However, monocytes can be involved in pathogenesis and drive inflammation and sequestration of infected red blood cells in organs such as the brain, placenta or lungs. Plasmodium components (including DNA, hemozoin or extracellular vesicles) can impair the function of monocytes. With time, reinfections with Plasmodium change the relative proportion of monocyte subsets and their physical properties. These changes relate to clinical outcomes and might constitute informative biomarkers of immunity. More importantly, at the molecular level, transcriptional, metabolic or epigenetic changes can ‘prime’ monocytes to alter their responses in future encounters with Plasmodium. This mechanism, known as trained immunity, challenges the traditional view of monocytes as a component of the immune system that lacks memory. Overall, this rough guide serves as an update reviewing the advances made on understanding of monocyte-malaria interactions during the past five years.